Forward-Forward Mean Field Games in Mathematical Modeling with Application to Opinion Formation and Voting Models - Adriano Festa; Simone Göttlich; Michele Ricciardi (Dynamic Games and Applications, 2024)
While the general theory for the terminal-initial value problem in mean-field games is widely used in many models of applied mathematics, the modeling potential of the corresponding forward-forward version is still under-considered. In this work, we discuss some features of the problem in a quite general setting and explain how it may be appropriate to model a system of players that have a complete knowledge of the past states of the system and are adapting to new information without any knowledge about the future. Then we show how forward-forward mean field games can be effectively used in mathematical models for opinion formation and other social phenomena.
Keywords: 330; Mean-Field Games; Hamilton-Jacobi equations; Fokker-Planck equations; Social mathematical models